Essential Readings in Light Metals 2013
DOI: 10.1002/9781118647851.ch54
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Various Methods for Modeling the Metal‐Bath Interface

Abstract: The correct evaluation of the stationary metal-bath interface in aluminum reduction cells is still a source of discussion and controversy. The objective of this paper is to present some calculations of the interface performed by different methods, used in software packages and to compare them with measured metalbath interface profile in a real cell. Our comparison includes Shallow Layer approach and 3D multiphase methods, such as: homogeneous and inhomogeneous volume of fluid (VOF) as well as floating grid met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…The proposed current density, centered in the centre channel, simulates the main characteristics of an aluminium reduction cell i.e. increasing current pick-up along the cathode block, corresponding in shape to that proposed by Severo et al [27].…”
Section: Propertiesmentioning
confidence: 75%
“…The proposed current density, centered in the centre channel, simulates the main characteristics of an aluminium reduction cell i.e. increasing current pick-up along the cathode block, corresponding in shape to that proposed by Severo et al [27].…”
Section: Propertiesmentioning
confidence: 75%
“…Considering the temperature and flow rate values reported in Ref. 7, it is concluded that if exfiltrations could be channeled in a single stream, then exfiltration heat could be available for thermal integration in the form of an airflow at $300°C. The amount of easily extractable heat is difficult to estimate since present furnaces are not designed to channel exfiltrations into a single stream; exfiltrations are currently dissipated into the surroundings.…”
Section: Waste Heat Sourcesmentioning
confidence: 99%
“…Similar to exfiltration temperatures, top surface temperatures vary with furnace sections (between 100°C and 1100°C) based on Ref. 7. Using temperature and heat flux data from individual furnace sections, an average temperature of 700°C is obtained for this heat source.…”
Section: Waste Heat Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoelectrodes arrays are studied by Godino et al 18 Magnetohydrodynamics of aluminum electrolysis cells were modeled by Severo and coworkers. 19 Electrochemical machining processes were simulated by Hardisty and Mileham. 20 Dees et al modeled lithium polymer batteries.…”
Section: Introductionmentioning
confidence: 99%